Η ιδεολογία της οικονομικής ανάπτυξης: Οι πρόσφυγες στο μεσοπόλεμο - Κωστής, Κ. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1992)
The contribution of the refugees to Greece’s economic development during the interwar period represents, at least up to the Second World War, a much argued upon and controversial subject. Their integration in the country’s political system gradually brought about the weakening of the controversy; in the end, the view that the refugees brought about important changes in the economic structures of Greece prevailed. Thanks to the refugees, this argument runs, Greece’s economy entered its industrial period, whilst their contribution to other economic sectors was extremely important as well. This opinion has become firmly established «common knowledge» and there are but few historians or social scientists who hold the view that things may not be exactly this way. In my paper, I tried to show that we are still far from being able to demonstrate the extent of the refugees’ contribution, if such a procedure can be considered methodologically possible, which I strongly doubt. What I do consider absolutely certain is that the refugees did not bring about the extraordinary transformations of Greece’s economy that public opinion ascribes to them. A careful examination of the economic indicators in a consistent theoretical context, — something overlooked by historians, who simply adopt the interwar statistics — easily proves that the refugees’ economic potential was integrated into Greece’s economic structures, themselves under the influence of the interwar conjecture. None of the economic sectors examined yield evidence of any radical transformation due to the influx of the refugees. Even in the case of the so-called fiscal burdening caused by the refugees’ rehabilitation, the data at our disposal are far too restricted for any categorical affirmations. Therefore, the dominant view of the refugees’ contribution to Greece’s economic development during the interwar period is to be considered as yet another myth that remains uncontested in Greek historiography.